2016
DOI: 10.3390/vaccines4040037
|View full text |Cite
|
Sign up to set email alerts
|

Is There Still Room for Cancer Vaccines at the Era of Checkpoint Inhibitors

Abstract: Checkpoint inhibitor (CPI) blockade is considered to be a revolution in cancer therapy, although most patients (70%–80%) remain resistant to this therapy. It has been hypothesized that only tumors with high mutation rates generate a natural antitumor T cell response, which could be revigorated by this therapy. In patients with no pre-existing antitumor T cells, a vaccine-induced T cell response is a rational option to counteract clinical resistance. This hypothesis has been validated in preclinical models usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 147 publications
0
35
0
Order By: Relevance
“…32 Various cancer vaccines combined with inhibitory pathway blockade have been validated in preclinical models, and enhanced T cell infiltration of various tumors has been demonstrated following this combination therapy. 50…”
Section: Discussionmentioning
confidence: 99%
“…32 Various cancer vaccines combined with inhibitory pathway blockade have been validated in preclinical models, and enhanced T cell infiltration of various tumors has been demonstrated following this combination therapy. 50…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several preclinical and clinical studies demonstrated synergistic effect of combinatorial blockade of two or more immune checkpoint molecules . Nevertheless, although checkpoint inhibitors are considered a revolution in the immunotherapy of cancer, depending on the tumor type, the majority of patients remain resistant to this therapy or relapse over time . Thus, as previously observed for cancer vaccines, only targeting one side of the balance will not be sufficient and therefore alleviating inhibition by checkpoint inhibitors will need to be combined with stimulating the immune system, using anticancer vaccines …”
mentioning
confidence: 99%
“…Numerous preclinical and clinical studies are ongoing and planned concerning the use of these checkpoint inhibitor antibodies in combination with other forms of therapy, including other immunotherapeutics. [12][13][14][15][16] Avelumab and atezolizumab are unique among currently employed anti-PD-L1 MAbs in that they are fully human immunoglobulin IgG1s with a non-mutated Fc, which also renders them capable of mediating antibody-dependent cell-mediated cytotoxicity (ADCC). 17,18 Several other MAbs currently employed in cancer therapy are also of the IgG1 isotype, including cetuximab, trastuzumab, and rituximab.…”
mentioning
confidence: 99%